A sequence starts with and the next term is .
If the further terms are given by
Then find the last 3 digits of .
Details :- If you don't know how to get the solutions for recurrence relations, you may try to learn it here .
This note will prove helpful in the coming problems of this series.
First Problem is bit easier than this one.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks to Danesh Chavan for his solution to the first problem of this series. Else, I would not be able to provide a solution here.
We have to change the form of the recurrent relation as follows:
a n = 7 a n − 1 − 1 0 a n − 2 + 7 ⇒ a n + b = a n = 7 ( a n − 1 + b ) − 1 0 ( a n − 2 + b ) ⇒ a n = a n = 7 ( a n − 1 + b ) − 1 0 ( a n − 2 + b ) − b ⇒ 7 b − 1 0 b − b = 7 ⇒ b = − 4 7
Therefore, a n − 4 7 = 7 ( a n − 1 − 4 7 ) − 1 0 ( a n − 2 − 4 7 ) and the characteristic polynomial is x 2 = 7 x − 1 0 ⇒ x 2 − 7 x + 1 0 = 0 ⇒ ( x − 2 ) ( x − 5 ) = 0
Then we have a n is of the following form:
a n − 4 7 = c 1 ( 2 n ) + c 2 ( 5 n ) ⇒ { a 0 − 4 7 = 0 − 4 7 = c 1 + c 2 a 1 − 4 7 = 1 − 4 7 = 2 c 1 + 5 c 2 ⇒ 2 c 1 + 2 c 2 = − 4 1 4 ⇒ 2 c 1 + 5 c 2 = − 4 3 . . . ( 1 ) . . . ( 2 ) E q . 2 − E q . 1 : 3 c 2 = 4 1 1 ⇒ c 2 = 1 2 1 1 ⇒ c 1 = − 3 8
Therefore, we have a n = 1 2 1 1 ( 5 n ) − 3 8 ( 2 n ) + 4 7
⇒ a 2 0 = 1 2 1 1 ( 5 2 0 ) − 3 8 ( 2 2 0 ) + 4 7 = 8 7 4 2 0 1 4 2 8 7 4 3 7 2